HUBUNGAN RESILIENSI AKADEMIK DENGAN TINGKAT STRES DALAM MENGERJAKAN SKRIPSI PADA MAHASISWA KEPERAWATAN TINGKAT AKHIR UNIVERSITAS RIAU - Permata Rigina Sonia; Bayhakki Bayhakki; Hellena Deli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Working on a thesis is an academic responsibility in obtaining a bachelor's degree. The obstacles faced in completing the thesis require resilience for students to avoid psychological problems such as stress. The purpose of this study was to determine the relationship between academic resilience and stress levels in doing thesis on nursing students at the 4th year of the University of Riau. This study used a cross sectional approach. The sample in this study was 119 people who were taken using random sampling technique. Data collection was taken using a questionnaire of academic resilience and stress levels. Data analysis used univariate and bivariate using chi square test. The results showed that the resilience of the students of the Faculty of Nursing, University of Riau who were working on theses mostly with low academic resilience (40.3%). The stress level of the students of the Faculty of Nursing, Riau University who are working on their thesis, most of the respondents with a severe stress level (78.2%). Based on statistical tests, it is proven that there is a significant relationship between academic resilience and stress levels of students from the Faculty of Nursing, Riau University who are working on their thesis with p value 0.000 < (0.05). There is a significant relationship between Academic Resilience and Stress Levels in Working on Thesis in Nursing Students at the University of Riau. Results Based on the research obtained, it is certain that students who work on theses can improve academic resilience to avoid stress in the completion process so that they can complete their studies on time.Keywords : Academic Resilience, Stress, Thesis